A natural history study of the prognostic role of coronary arteriography - Brymer, James F.; Buter, Thomas H.; Walton, Joseph A.; Willis, Park W. (The American heart journal, 1974)
Coronary cinearteriograms, clinical records, and left ventriculograms of 304 patients studied for evaluation of chest pain were reviewed. Clinical and follow-up data on survival of the normal subjects and the nonoperative group with abnormal arteriograms are presented. Ninety-two per cent of patients with typical angina pectoris had serious coronary occlusive disease. Ninety-eight per cent of patients with relatively normal coronary arteriograms survived for one to 60 or more months (mean follow-up period 24 months). There was a high mortality rate when the left main coronary artery was involved (47 per cent) and when the left coronary anterior descending branch was seriously occluded (28 per cent when arteriographic scores were high and 14 per cent when total scores were low) and a low mortality rate (0 to 7 per cent) when the LAD was normal. Mean follow-up interval in these groups was 19 months. The mortality rate was nearly three times greater when patients had QRS changes on ECG of prior myocardial infarction and six times greater when left ventricular contraction was significantly impaired.